Acute vestibular syndrome induced by supratentorial stroke: clinical features and network compensation mechanisms - Pan, Songbin; Zhang, Yisi; Ding, Xian; Pan, Xiaofeng; Chen, Xiaoguang; Lv, Xiaoqiang; You, Hong; Zhu, Junyv (Frontiers in Neurology, 2025)
IntroductionIt remains unclear which vestibular symptoms and signs are associated with supratentorial stroke presenting as acute vestibular syndrome, and whether there is hemispheric predominance in the manifestation of these symptoms and signs.MethodsThis prospective study aims to further characterize the clinical features and explore the underlying mechanisms of acute vestibular syndrome (AVS) in patients caused by supratentorial stroke by integrating the findings from neuro-otological and neuro-ophthalmological examinations.ResultsThis study ultimately included 13 patients with AVS were confirmed supratentorial stroke by diffusion weighted imaging(DWI). Infarction involved only the cortical areas in 7 patients, only the subcortical structures in 5 patients, and both regions in 1 patient. 61.5% (8/13) of patients exhibited at least one abnormal neuro-otological or neuro-ophthalmological finding, including smooth pursuit test (n = 2), optokinetic test (n = 3), saccades test (n = 2), caloric test (n = 2), video head impulse tests (n = 3).DiscussionLesions showed left hemispheric predominance overall, but no clear hemispheric predominance for specific symptoms (50% of vertigo lesions were right-sided). Vertigo was associated with cortical lesions (4/4), while dizziness more often involved subcortical structures (6/9), suggesting different mechanisms: acute disruption of vestibular-visual integration versus impaired vestibulo-cortical signaling via basal ganglia-thalamo-cortical circuits. In summary, AVS induced by supratentorial stroke results from the interplay between multimodal network impairment and dynamic compensation. The study highlights the need to incorporate detailed vestibular testing beyond HINTS to avoid missing supratentorial stroke in AVS patients, despite limitations like small sample size.